2013
DOI: 10.1371/journal.pone.0083012
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating Emergence and Transmission of Multidrug-Resistant Tuberculosis in Treatment Experienced Patients by Whole Genome Sequencing

Abstract: BackgroundUnderstanding the emergence and spread of multidrug-resistant tuberculosis (MDR-TB) is crucial for its control. MDR-TB in previously treated patients is generally attributed to the selection of drug resistant mutants during inadequate therapy rather than transmission of a resistant strain. Traditional genotyping methods are not sufficient to distinguish strains in populations with a high burden of tuberculosis and it has previously been difficult to assess the degree of transmission in these settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 50 publications
6
69
0
1
Order By: Relevance
“…With the ever-decreasing cost of bacterial genome sequencing-a recent review noted that, in some extreme cases, the cost of generating a single draft assembly is now less than one dollar 35 -it can be tempting to see sequencing as the hammer for every nail. However, before deciding to launch 26 2 Schürch et al 159 3 Gardy et al 27 36 Bryant et al 160 199 Bryant et al 143 94 Clark et al 161 51 Kato-Maeda et al 162 9 Roetzer et al 139 86 Torok et al 163 2 Walker et al 29 390 Jamieson et al 19 36 Kohl et al 164 26 Luo et al 165 32 Mehaffy et al 166 61 Pérez-Lago et al 148 36 Walker et al 167 247 Coscolla et al 168 46 Glynn et al 169 170 Guerra-Assunção et al 170 1687 Guerra-Assunção et al 144 1933 Lee et al 171 120 Lee et al 172 163 Regmi et al 173 9 Stucki et al 174 3 Witney et al 175 16 Arnold et al 138 2 Outhred et al 176 22 a genomic epidemiology study, several questions must be answered. First, is sequencing even possible?…”
Section: Step 1: Look Before You Leapmentioning
confidence: 99%
“…With the ever-decreasing cost of bacterial genome sequencing-a recent review noted that, in some extreme cases, the cost of generating a single draft assembly is now less than one dollar 35 -it can be tempting to see sequencing as the hammer for every nail. However, before deciding to launch 26 2 Schürch et al 159 3 Gardy et al 27 36 Bryant et al 160 199 Bryant et al 143 94 Clark et al 161 51 Kato-Maeda et al 162 9 Roetzer et al 139 86 Torok et al 163 2 Walker et al 29 390 Jamieson et al 19 36 Kohl et al 164 26 Luo et al 165 32 Mehaffy et al 166 61 Pérez-Lago et al 148 36 Walker et al 167 247 Coscolla et al 168 46 Glynn et al 169 170 Guerra-Assunção et al 170 1687 Guerra-Assunção et al 144 1933 Lee et al 171 120 Lee et al 172 163 Regmi et al 173 9 Stucki et al 174 3 Witney et al 175 16 Arnold et al 138 2 Outhred et al 176 22 a genomic epidemiology study, several questions must be answered. First, is sequencing even possible?…”
Section: Step 1: Look Before You Leapmentioning
confidence: 99%
“…In the case of ethambutol resistance, a study showed that a low-level resistance that would be undetected by current phenotypic antibiotic susceptibility testing may accumulate within the genome of M. tuberculosis (41). In contrast, another study reported that phenotypic testing indicated isoniazid resistance, but WGS failed to identify the mutation responsible (45). Mutations conferring drug resistance are known to come at the cost of a loss in an organism's fitness; however, recent genomic studies revealed that compensatory mutations can occur which overcome the loss of fitness and create a "perfect storm" of resistant isolates without reduced fitness (42,(46)(47)(48).…”
Section: Genomics For Predicting Antibiotic Susceptibility Of M Tubementioning
confidence: 99%
“…Des difficultés demeurent quant à la généralisation de l'approche du séquençage haut-débit dans l'élucidation de maladies infectieuses, excluant dans l'immédiat une utilisation en routine. Malgré tout, pour des applications particulières, telles que la prise en charge d'infections à bactéries multirésistantes, le recours au séquençage haut-débit est envisagé à large échelle [8,9]. • L'élucidation des cas de co-infections ; le séquençage haut-débit permet de séquencer le microorganisme prédominant ainsi que les microorganismes minoritaires, rendant possible l'identification et la caractérisation de variants rares.…”
Section: Laboratoire De Microbiologie : Gagner Du Temps Pour Un Traitunclassified